En vegg av tekst - Furu, Iris (Klart språk i Norden, 2014)
Iris Furu presents findings from her master’s thesis in Rhetoric and Communication in which she studies the language used in different kinds of informing texts and forms from NAV, the Norwegian Labour and Welfare Administration. Expecting parents in Norway can apply for parental benefits from NAV by filling out a specific form. What makes these forms the way they are, and do Norwegian parents understand how to fill them out? Through qualitative interviews with both NAV employees and Norwegian citizens, Furu has provided a closer look into the communication processes between the state and the citizens in Norway. By looking at the statements from both sender and recipient she has been able to show what happens when the communication between the system and the user is successful – and when it fails.